The influence of celebrity endorsement on actual purchase behaviour with mediating role of brand equity: A study on local food brands - Nur Shazzana, Ahmad Shaker (2015)
With fiercely intense competition, having a good product alone seems inadequate to sustain and be among the top notch product in the market. To do so, marketing strategy of most business firms relies heavily on advertising to promote their products and capitalize the most prominent technique in this modern era which is the use of celebrity endorsement. Nowadays, celebrities are claimed as the most influential icons that people admire and easily attracted to. This influential power has seen to give a huge impact on most businesses especially by strengthening the company’s or product’s brand. In the meantime, having an excellent brand is considered as the most valuable asset for a company. It can be achieved by managing the brand equity in the right way. This intangible asset provides value for both the consumer and the firm. It is believed that having attractive advertising strategy that capitalizes celebrity endorsement to promote the products may increase the value of the brand which in turn can stimulate consumers to buy. Therefore this research is conducted to gain insight into the influence of celebrity endorsement towards actual purchase behaviour of consumers and investigating the impact of brand equity as the mediating variable between these two constructs. This study also intended to explore the Malaysian food brands specifically for the packaged food products. It is certainly undeniable that our local food brands still cannot compete with international origin brands. National brands are deemed as unfamiliar and unattractive enough to win the heart of consumers. Due to this crucial issue, research is conducted to examine the consumers’ purchasing behaviour of local food brands. In fact, the purpose of this research is to figure out the dimensions of celebrity endorsement that highly influence consumer’s actual purchase behavior and whether the presence of brand equity will mediate the relationship between celebrity endorsement and actual purchase behaviour of local food brands. To achieve the objectives, questionnaire was constructed and distributed to 300 respondents in Penang. Findings shown that celebrity endorsement has significant relationship with actual purchase behaviour and attractiveness of celebrity becomes the major factor in influencing consumers to buy local food brands. Results also revealed that brand equity mediates the relationship between celebrity endorsement and actual purchase behaviour and brand awareness is the most influential factor towards this relationship.